Development of Digital Substations and Modern Networks - Hamidova, Ayshan (ADA University, 2023)
A link for the effective integration of renewable energy sources into electrical networks is provided by substations, which have been used extensively over the past few years in the application of renewable energy sources. The amount of power generated determines how well RES are incorporated into the utility grid.[1] The digitization of substations has therefore grown even more in demand and desirable. The security of resources and labor are given the greatest consideration, along with economic aspects. Utilizing new instruments, methods, and processes at substations to improve operational efficiency is possible for the power industry thanks to digitization.[2] The simplest definition of "intelligent networks" might be defined as electric grids that effectively integrate the behavior and attempts of all linked points (those who generate electricity, those who consume it, and those who perform both actions) to supply a safe, affordable electricity consumption.[3] Process monitoring, power flow regulation, and electrical system component protection are among the functions of these integrated systems. For example, communication networks are used to link electrical system automation devices with supervisory systems and other devices in order to exchange data. One of the important areas of research is the study of the problem of reliability and efficiency of energy supply to consumers, and the determination of the main influencing factors. The development of industrial, agricultural and household sectors directly depends on the reliability of energy supply. Schemes of electric networks should ensure the necessary reliability of electric power supply, the transmission of the required amount with indicators of the quality of electric power to consumers, further development of the network and the connection of new consumers, convenience and safety of operation. Electrical installations used for the transformation, transmission and distribution of electric energy are subject to the influence of many factors. These factors can be environmental, operational, accidental, design and construction defects.[3] Delivering dependable and secure electricity to consumers is the goal of the contemporary electrical network. As dispersed generation becomes more prevalent and technology advances, the current distribution system becomes increasingly decentralized and complex. As carbon emissions and global warming rise, the integration of renewable energy sources into the electrical grid is accelerating. Because the distribution system has a direct line to the clients, reliability is one of its most crucial components. The current distribution system is having numerous issues as a result of system malfunctions. [4]. This paper examines aspects of reliability and sustainability for the further improvement and development of digital substations and transmission systems. Thus, the digital substation operates better in addition to medium-sized sources being established and solar panels being used
Keywords: Power systems -- Digitization; Energy policy -- Environmental aspects; Electric substations -- Automation; Smart power grids; IT and Engineering